Perlindungan Hukum Korban Penyalahgunaan Dan Pecandu Narkotika Dari Perspektif Filsafat Hukum Sub Hukum Progresif - Diyanto, Diyanto; Rahmat, Diding; Sudarto, Sudarto (LITERATUS, 2025)
In the life of the nation and the state, Indonesian citizens have the right to obtain fair legal certainty and equal treatment before the law, as guaranteed in Article 28D paragraph (1) of the 1945 Constitution. This study aims to examine the legal protection for victims of drug abuse and addicts in Indonesian legislation from the perspective of legal philosophy, particularly progressive law. The research uses two legal research methods: normative legal research (juridical-normative) and empirical legal research (sociolegal studies). The findings show that victims of drug abuse and addicts possess constitutional rights to receive medical and social rehabilitation, as stipulated in Articles 54, 55, 103 in conjunction with Article 127 of Law No. 35 of 2009 on Narcotics and relevant articles in Law No. 1 of 2023. A case study of Supreme Court Decision No. 109 PK/Pid.Sus/2023 demonstrates the application of a progressive legal approach, where the judge prioritized the principle of “law that humanizes humans” as a fundamental consideration in overturning the previous decision and granting the judicial review.